Three times the lesser of two consecutive even integers is 6 less than six times the greater number. Find the integer.

**x = first even integer**

x + 2 = second even integer

x + 2 = second even integer

3x = 6(x + 2) - 6 {three times the lesser is six less than six times the greater}

3x = 6x + 12 - 6 {used distributive property}

3x = 6x + 6 {combined like terms}

-3x = 6 {subtracted 6x from each side}

x = -2 {divided each side by -3}

x + 2 = 0 {substituted 0, in for x, into x + 2}

**-2 and 0 are the two even integers**

Assuming you are classifying 0 and -2 as even integers, it works.

__Ask the House__